Personal solar ultraviolet radiation dosimetry in an occupational setting across Europe. (10th March 2020) - Wittlich, M.; John, S.M.; Tiplica, G.S.; Sălăvăstru, C.M.; Butacu, A.I.; Modenese, A.; Paolucci, V.; D'Hauw, G.; Gobba, F.; Sartorelli, P.; Macan, J.; Kovačić, J.; et al.
Abstract: Background: Work‐related solar ultraviolet radiation (UVR) is an important factor in the pathogenesis of non‐melanoma skin cancer (NMSC). The World Health Organization, through the International Agency for Research on Cancer, has classified solar UVR as a group 1 carcinogen since 2012. The main problems encountered so far in the study of occupationally induced skin cancer include the lack of accurate occupational UVR dosimetry as well as insufficient distinction between occupational and leisure UVR exposure and underreporting of NMSC. Objectives: The aim of this study was to collect long‐term individual UVR measurements in outdoor workers across European countries. Methods: A prospective study was initiated through the European Academy of Dermatology and Venereology, Healthy Skin@Work Campaign, measuring UVR exposure doses at occupational settings of masons from five European countries. Measurements were performed for several consecutive months using the GENESIS‐UV measurement system. Results: The results identified alarming UVR exposure data. Average daily UVR doses ranged 148.40–680.48 J/m 2 in Romania, 342.4–640.8 J/m 2 in Italy, 165.5–466.2 J/m 2 in Croatia, 41.8–473.8 J/m 2 in Denmark and 88.15–400.22 J/m 2 in Germany. Results showed an expected latitude dependence with increasing UVR yearly dosage from the north to the south of Europe. Conclusions: This study shows that outdoor workers from EU countries included in this study are exposed to high levels of occupational solar UVR, vastly exceeding the occupational exposure limits for solar UVR exposure, considered to be 1–1.33 SED/day in the period from May to September. This finding may serve as an evidence‐based recommendation to authorities on implementing occupational skin cancer prevention strategies.